Adherence to Cultural Norms and Economic Incentives: Evidence from Fertility Timing Decisions - Bastien Chabé-Ferret (Institute for the Study of Labor (IZA), 2016)
I analyze the interplay between culture and economic incentives in decision-making. To this end, I study birth timing decisions of second generation migrant women to France and the US. Only the probability to have three or more children increases with the home country fertility norm, whereas the timing of the first two births is either unaffected or negatively correlated. I propose a model that rationalizes these findings in which decisions are the result of a trade-off between an economic cost-benefit analysis and a cultural norm. The model predicts that decisions with a higher cost of deviation from the economic optimum should be less prone to cultural influence. This is consistent with substantial evidence showing that the timing of the first birth bears much larger costs for mothers in terms of labor market outcomes than that of subsequent births.
Keywords: J13; J15; Z10; Z12; 330; cultural norms; fertility; birth timing